KEBUTUHAN PERAWATAN ORTODONSI BERDASARKAN INDEX OF ORTHODONTIC TREATMENT NEED DI SMP KATOLIK THEODORUS KOTAMOBAGU - Hansu, Christy; Anindita, P. S.; Mariati, Ni Wayan (e-GiGi, 2013)
Abstract: In the year of 1995 World Health Organization (WHO) counted the prevelensi needs of orthodontic treatment in 10 industrial countries, where the needs of the orthodontic treatment around 21-64%. At this time they have never done the research of the needs of orthodontic treatment in the city of Kotamobagu. This research aims to measure the requirement of orthodontic treatment based on Index of Orthodontic Treatment Need (IOTN). IOTN consists of two parts: Aesthetic Component ( AC) and Dental Health Component ( DHC). This is a descriptive observational study, conducted in Theodorus Catholic junior high school Kota Kotamobagu in April 2013. The population consist of all Theodorus Catholic junior high school students between 13-14 years old that are 222 students and only 143 students are includes in the sampling frame. Samples were then checked by use IOTN (AC and DHC). The results showed that based on the AC, 95% no need treatment or mild treatment, 4.2% need borderline treatment and 0.7% great need treatment while on DHC, 85.3% no need treatment or only light treatment, 13.3% need borderline treatment and 1.4% great need treatment. The results of AC shows less valid because the AC just measured subjectively by judging only by the looks of the patients teeth, compare to the DHC where we measure objectively by checking and measuring the condition of the teeth and mouth. With that said the result of this research shows that they who has their teeth from the AC angle looks good, but from the DHC angle they need treatment. Keywords: Index of Orthodontic Treatment Need, Aesthetic Component, Dental Health.